Macroinvertebrates and phytoplanckton as bioindicators of pollution in Chicama river basin, Peru - Santillán-Aredo, Santos R. (2018)
The principal objective was to assess phytoplankton and macroinvertebrates as bioindicators of pollution in Chicama river basin, Peru. Was developed four stations and was assess macroinvertebrates by Trent Biotic Index and Chandler Biotic Score, and it was assess the abundance of taxa related to the variables measures, to establish the relationship between the variables with the Spearman correlation coefficient. The assessment of the phytoplankton are carried out through the index proposed by Pantle and Buck; similarly, the index was calculated from Shannon Weaver (H´) and the index of Simpson (D´). It was registered 24 genera of benthuc fauna, 18 families and 9 orders, with a predominance of Baetis sp., Rhagovelia sp. and Atopsyche sp. and to a lesser degree, in comparison with its predecessors, Tricorythodes sp., Clinotanypus sp., and Simulium sp. In regards phytoplankton was composed mainly by diatoms (Bacillariophyta) and some species belonging to the class Chlorophyta, with predominance of Nitzschia linearis, Fragilaria capucina and Gomphonema sp. Finally, the indices evaluated, Trent biotic index and Chandler Biotic Score determined that there is from slight to moderate pollution according to the index of Pantle and Buck.